Properties of Y-Shaped PFO-DBT Nanotubes - Fakir, M.S.; Supangat, A.; Sulaiman, K. (Hindawi Publishing Corporation, 2014)
Immersion of template into solution is used to synthesize the Y-shaped poly[2,7-(9,9-dioctylfluorene)-alt-4,7-bis(thiophen-2-yl)benzo-2,1,3-thiadiazole] (PFO-DBT) nanotubes. Solution annealing and different aging times (1, 24, and 72 hours) are conducted to synthesize the Y-shaped PFO-DBT nanotubes and the effects on the morphological, structural, and optical properties of Y-shaped PFO-DBT nanotubes are investigated. The dense, aligned, and elongated Y-shaped PFO-DBT nanotubes have been successfully fabricated by aging the PFO-DBT solution for 72 hours. Enhanced light absorption with less light scattering can be exhibited from the elongated Y-shaped PFO-DBT nanotubes. Partial and complete infiltration is governed by 1 hour and 72 hours of aging time, respectively. Preformed nanofibres are initiated by the process of annealing and aging of PFO-DBT solution. During the aging process, PFO-DBT nanofibres are formed to coat the pores’ wall and replicated the Y-branched nanopores for the production of Y-shaped PFO-DBT nanotubes. The effects of solution annealing and aging process are essential for the improvement on the morphological, structural, and optical properties of Y-shaped PFO-DBT nanotubes.